Study of Ovary Follicular Profile and Estrogen Concentration of Peranakan Ongole (PO) Cows at Estrous Phase in Mountains and Lowland at Kulon Progo District, Yogyakarta - Fani, Rifia Tiara; Budiyanto, Agung; Kusumawati, Asmarani (Jurnal Sain Veteriner, 2024)
Ovarian follicle dinamycs and estrogen concentration interrelated to cow reproduction traits. Some previous studies said that preovulatory follicle directly related to estrogen concentration which induce estrous quality, and increasing pregnancy rate when artificial insemination happened. Another important factor to optimizing reproduction performance is altitude. Here in Indonesia these factors has not been studied further in PO cows. A total of 24 Peranakan Ongole (PO) cows, 12 cows from highlands or mountains of Kalibawang, Kulon Progo, Yogyakarta, Indonesia and 12 cows from lowlands or lowland of Galur District, Kulon Progo, Yogyakarta, Indonesia selected based on criterias; these cows ever had calves, not pregnant, 3-8 years old, have a Body Condition Score (BCS) of 2.5-3.5, in the peak phase of estrus and not experienced reproductive problems. The diameter of the cow ovarian follicles were examined using ultrasound and sera were taken to calculated the estrogen concentration using ELISA, meanwhile the NSPC taken from recording and farmer interview. The result showed that no difference of follicle diameter and estrogen concentration between mountain and lowland (p>0,05), a significant difference found in NSPC between mountain and lowland (p<0,05), and a strong correlation found betweend follicle diameter, estrogen concentration and NSPC (p<0,05), proved that the larger the follicle diameter, the higher the estrogen level and will improve the reproductive trait of PO cows.